#### Answer

x=6

#### Work Step by Step

Simplifying
3x + -4(x + -3) = 3(x + -4)
Reorder the terms:
3x + -4(-3 + x) = 3(x + -4)
3x + (-3 * -4 + x * -4) = 3(x + -4)
3x + (12 + -4x) = 3(x + -4)
Reorder the terms:
12 + 3x + -4x = 3(x + -4)
Combine like terms: 3x + -4x = -1x
12 + -1x = 3(x + -4)
Reorder the terms:
12 + -1x = 3(-4 + x)
12 + -1x = (-4 * 3 + x * 3)
12 + -1x = (-12 + 3x)
Solving
12 + -1x = -12 + 3x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-3x' to each side of the equation.
12 + -1x + -3x = -12 + 3x + -3x
Combine like terms: -1x + -3x = -4x
12 + -4x = -12 + 3x + -3x
Combine like terms: 3x + -3x = 0
12 + -4x = -12 + 0
12 + -4x = -12
Add '-12' to each side of the equation.
12 + -12 + -4x = -12 + -12
Combine like terms: 12 + -12 = 0
0 + -4x = -12 + -12
-4x = -12 + -12
Combine like terms: -12 + -12 = -24
-4x = -24
Divide each side by '-4'.
x = 6
Simplifying
x = 6